Genomic signatures in B-cell lymphoma: How can these improve precision in diagnosis and inform prognosis?. Issue 2 (March 2016) - Iqbal, Javeed; Naushad, Hina; Bi, Chengfeng; Yu, Jiayu; Bouska, Alyssa; Rohr, Joseph; Chao, Wang; Fu, Kai; Chan, Wing C.; Vose, Julie M.
Abstract: Current genomic technologies have immensely improved disease classification and prognostication of major subtypes of B-cell lymphomas. This novel genetic information has not only aided in diagnosis, but has also revealed a landscape of critical molecular events that determine the biological and clinical behavior of a lymphoma. In this review, we summarized the genetic characteristics of major subtypes of B-cell lymphomas, including diffuse large B cell lymphoma (DLBCL), follicular lymphoma (FL), Burkitt lymphoma (BL), and mantle cell lymphoma (MCL). We illustrated how genomic profiling had identified molecular subgroups in DLBCL with varied clinical outcomes, and how a subset of genes defined prognosis in MCL and aided in BL diagnoses. We also highlighted some Phase II/III clinical trials using new therapeutic agents to determine clinical efficacy in novel molecular subgroups with distinct gene expression patterns. We believe that refinement of genomic signatures will require more intensive efforts from the biomedical research community to improve targeted therapy designs and bring a substantial change in the treatment decisions. In the next era of genomic medicine, we anticipate that a clinically and biologically relevant molecular profile of each tumor will be obtained at diagnosis to guide therapy.